Effect of Superthermal Species on Critical Mach Number and Small-Amplitude Solitary Waves in Dusty Plasmas - Acharya, Num P.; Khanal, Raju (Journal of Nepal Physical Society, 2025)
Dusty plasmas are plasmas that contain charged dust particles, in addition to the usual ions and electrons, and are found in space, industry, and laboratory experiments. Due to their omnipresence, studying them helps us understand natural phenomena such as planetary rings, comet tails, and interstellar clouds, as well as improve plasma-based technologies on Earth. In this work, we investigate the critical Mach number Mcr and small-amplitude solitary wave structures in an unmagnetized dust-acoustic waves (DAWs) dusty plasma with superthermal kappa-distributed electrons κe and ions κi . Using the Sagdeev pseudopotential approach, we analyze the effects of superthermal species, the ratio of dust to electron temperature σd , and the concentration of ion density δi . The results show that the critical Mach number is affected by superthermal species and the ratio of dust to electron temperature. The amplitude and width of small-amplitude solitary waves are also affected by the Mach number M and the concentration of the ion density. These findings are relevant for understanding nonlinear wave dynamics in space and astrophysical dusty plasma environments.